Successful term delivery after Khairy’s modified B-lynch suture technique: First case rep - Ahmed M. Abbas; Amera M. Sheha; Mohamed K. Ali; Mohamed Khalaf; Esraa Gamal (Middle East Fertility Society Journal, 2017)
Postpartum hemorrhage (PPH) is a life-threatening obstetric complication. Uterine atony is the most common cause presenting in approximately 80% of cases. As regards management options, B-lynch brace suture, and its modifications have been used for more than a decade with a great success as a substitution for hysterectomy. Their efficiency in preserving future fertility is not well-established. This case reports the first successful pregnancy and delivery after one of the recent B-lynch suture modifications “Khairy’s modification” for control of atonic PPH during cesarean delivery. The patient got pregnant two months after the surgery. The course of pregnancy was smooth and she was delivered by Repeat cesarean section with no deformities of uterine cavity or contour. Khairy’s modified B-lynch suture is an effective technique that has no reported complications of the classic B-lynch suture or affection of subsequent fertility.